Antipsychotic treatment and the Rorschach Perceptual Thinking Index (PTI) in psychotic disorder patients: Effects of treatment. (May 2017) - Biagiarelli, Mario; Curto, Martina; Di Pomponio, Ileana; Comparelli, Anna; Baldessarini, Ross J.; Ferracuti, Stefano
Abstract: The Rorschach-based Perceptual Thinking Index (PTI) is used to identify and rate features of psychotic disorders, but effects of antipsychotic treatment on such ratings is not clear. Accordingly, we examined potential effects of antipsychotic drugs on PTI measures in 114 patients with a psychotic or bipolar-I disorder. Use and doses of antipsychotic drugs (as chlorpromazine-equivalent [CPZ-eq] mg/day) were unrelated to PTI total or subscale scores in any diagnostic group. PTI scores were independently and significantly associated with psychotic symptomatic severity (PANSS score) and less with female sex. These findings support the validity and value of the PTI in identifying features of psychosis even in the presence of antipsychotic treatment. Highlights: We evaluated the effects of the antipsychotic doses on the Rorschach PTI in psychosis. Antipsychotic doses did not correlate with Rorschach PTI and its main variables. PTI validity in psychosis assessment is not affected by antipsychotic administration.